Coordenação locomotora de indivíduos pós acidente vascular encefálico - Celestino, Melissa Leandro (2019)
Stroke survivors commonly present modified locomotor coordination, and protocols for gait training with partial body weight support (BWS) are usually employed. Diminished knee flexion on the paretic limb is one of gait alterations in those individuals and as such it influences the locomotor coordination. Quantify gait impairment would favor the understanding and development of training protocols for this population. The goal of this thesis was to investigate inter-limb locomotor coordination of individuals with stroke. Based upon that, three mainly concerns are raised: (1) the alterations in locomotor coordination in individuals with stroke are predominant during stance or swing balance? (2) The BWS training in different surfaces could provide alterations in locomotor coordination in individuals with stroke? (3) Non-disable individuals could present locomotor coordination similarly to individuals with stroke, if was manipulate their speed walk and the movement of knee flexion? In this way, three different studies were performed with individuals with stroke and individuals with no gait. For all experiments, the vector coding technique was employed and the frequency of coordination modes, such as in-phase, anti-phase, proximalsegment- phase, distal-segment-phase were analyzed. Overall, the results revealed that individuals with stroke present different intra-limb locomotor coordination for both thing-shank and shank-foot from their peers, and the differences are more pronounced in the distal limbs and during the swing period; gait training with BWS had not changed locomotor coordination in individuals with stroke in neither surface (i.e. treadmill and over the ground); slower speed and knee flexion constraint influenced locomotor coordination of individuals with no gait impairment, and the motor pattern was similar to individuals with stroke in some aspects and mainly between lower limbs. We conclude that the alteration of locomotor coordination in individuals with stroke, could be related mainly with the distal segments; the surface (overground or treadmill) do not change in the locomotor coordination training with BWS; finally, that slow velocity and knee movement restricted as manipulations caused similarities in non-disable walk and the hemiparetic walk, been a helpful information to futures protocols clinicians in rehabilitation.